2019
DOI: 10.1002/pola.29409
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polylactide‐PAMAM “Janus‐type” linear‐dendritic hybrids

Abstract: Herein, we present a facile and comprehensive synthetic methodology for the preparation of polyester‐polyamidoamine (PAMAM) (i.e., polyester: polylactide [PLA] (hydrophobic) and polyamidoamine, PAMAM [hydrophilic]) polymers. A library of PLA‐PAMAM linear dendritic block copolymers (LDBCs) in which both l and d, l polylactide were employed in mass ratios of 30:70, 50:50, 70:30, and 90:10 (PLA:PAMAM) were synthesized and analyzed. When placed in aqueous media, the immiscibility of the hydrophilic and hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 78 publications
2
36
1
Order By: Relevance
“…A general synthetic scheme for the PAMAM‐FA amphiphilic JDs, FA‐PAMAM‐NH 3 + , FA‐PAMAM‐COO − , FA‐PAMAM‐OH, and their precursors, FA‐PAMAM‐BOC, FA‐PAMAM‐TBE, FA‐PAMAM‐THP, is shown in Scheme 1. In our previous work, [32] we observed that amphiphilic block copolymers with 70 : 30 hydrophobic to hydrophilic ratio self‐assemble into bilayer vesicles in water. Based on our observations as well as those of polymer physics, [32,39,40] the molar mass of JDs was designed to keep 70 : 30 hydrophobic to hydrophilic weight ratio between the dendrons to yield more biologically relevant nanoaggregates [41] …”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…A general synthetic scheme for the PAMAM‐FA amphiphilic JDs, FA‐PAMAM‐NH 3 + , FA‐PAMAM‐COO − , FA‐PAMAM‐OH, and their precursors, FA‐PAMAM‐BOC, FA‐PAMAM‐TBE, FA‐PAMAM‐THP, is shown in Scheme 1. In our previous work, [32] we observed that amphiphilic block copolymers with 70 : 30 hydrophobic to hydrophilic ratio self‐assemble into bilayer vesicles in water. Based on our observations as well as those of polymer physics, [32,39,40] the molar mass of JDs was designed to keep 70 : 30 hydrophobic to hydrophilic weight ratio between the dendrons to yield more biologically relevant nanoaggregates [41] …”
Section: Resultsmentioning
confidence: 90%
“…GPC of protected JDs confirmed the absence of free dendrons that had not reacted during the CuAAC process by having a single peak in the chromatographs. Shoulders appearing adjacent to the main peak in the GPC trace are due to the branching nature of the dendrimer affecting its elution in the column (Figures S37–39) [32] . The dispersity values range from 1.02–1.06, which indicates the presence of monodisperse polymers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations